1985
DOI: 10.1002/j.1460-2075.1985.tb03909.x
|View full text |Cite
|
Sign up to set email alerts
|

Translation efficiency of zein mRNA is reduced by hybrid formation between the 5′- and 3′-untranslated region

Abstract: The secondary structure of zein mRNA affects its translational potential. Here we show that in a cell‐free system the translation efficiency of zein mRNA containing inverted repeats in the 5′‐ and 3′‐untranslated regions is reduced. This translational block is released after deletion of the 3′‐inverted repeat. We conclude that the translational block is caused by hybrid formation between the two inverted repeats. The translational efficiency of zein mRNAs, is also affected by varying the length or the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
2

Year Published

1987
1987
2001
2001

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 40 publications
4
27
0
2
Order By: Relevance
“…This may suggest a direct involvement of O2 in the transcription of some members of the other subsets (presently under investigation) or an indirect effect of the lowered zH polypeptide accumulation on the intracellular stability of macromolecules and of other storage proteins because of improper filling in of the protein bodies. In this respect translatability and stability of zein mRNA could impact zein polypeptides accumulation (Spena et al, 1985;Plotnikov and Bakaldina, 1996) and partly explain zein pattern variations among GBs. The studies on light-and heavy-zein transcript stabilities in the W64A GB carrying the O2w1 allele or the o2T allele indicated that the half-life of the two transcript populations is different with, however, an higher stability for the light transcripts in the mutant genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may suggest a direct involvement of O2 in the transcription of some members of the other subsets (presently under investigation) or an indirect effect of the lowered zH polypeptide accumulation on the intracellular stability of macromolecules and of other storage proteins because of improper filling in of the protein bodies. In this respect translatability and stability of zein mRNA could impact zein polypeptides accumulation (Spena et al, 1985;Plotnikov and Bakaldina, 1996) and partly explain zein pattern variations among GBs. The studies on light-and heavy-zein transcript stabilities in the W64A GB carrying the O2w1 allele or the o2T allele indicated that the half-life of the two transcript populations is different with, however, an higher stability for the light transcripts in the mutant genotype.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that the amount of heavy chain polypeptides determined at a given stage of development or at maturity represents an accumulation. On the contrary the transcript datum represents a steady-state level, which should not necessarily reflect the final abundance of H polypeptides, as cytoplasmic control mechanisms for the translational efficiency of zH mRNA have been put forward (Spena et al, 1985;Kodrzycki et al, 1989). Table I).…”
Section: Heavy Chain Zein Transcripts Occur In O2 Linesmentioning
confidence: 99%
“…Long-range base pairings are known to form in some bacterial transcripts (2,3,25), and there is one published report of repression of eucaryotic translation in vitro by pairing between 5' and 3' noncoding sequences (33). Here I show that inhibition of translation by long-range interactions can also be demonstrated in the cytoplasm of transfected cells, where the inhibition depends on the composition of the culture medium and, in an interesting way, on the precise location of the complementary sequences within the mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In higher eucaryotes, translational efficiency has been correlated with the accessibility of the 5' cap (9,10). In addition, translational efficiency of zein mRNA is reduced by duplex formation between the 5'-and 3'-untranslated regions (51). Duplex formation between 5'-and 3'-untranslated regions could explain the diminished translation of mRNA from certain cycl-512 revertants (64).…”
Section: Discussionmentioning
confidence: 99%